The Janus Effect of Generative AI: Charting the Path for Responsible Conduct of Scholarly Activities in Information Systems - Susarla, Anjana; Gopal, Ram; Thatcher, Jason Bennett; Sarker, Suprateek (Information Systems Research, 2023)
Funding: A. Susarla was funded by an R01 grant from the National Library of Medicine, through [Grant R01LM013443].